2015
DOI: 10.1002/bimj.201400233
|View full text |Cite
|
Sign up to set email alerts
|

Zero‐inflated regression models for radiation‐induced chromosome aberration data: A comparative study

Abstract: yliveir D w r¡ % nd iin e kD to hen nd riguer sD w nuel nd eins uryD iliz eth nd uigD edro nd othk mmD u i @PHITA 9 eroEin) ted regression models for r di tionEindu ed hromosome err tion d t X omp r tive studyF9D fiometri l journ lFD SV @PAF ppF PSWEPUWFFurther information on publisher's website:httpXGGdxFdoiForgGIHFIHHPG imjFPHIRHHPQQPublisher's copyright statement:his is the epted version of the following rti leX yliveir D w r¡ % D iin e kD to henD riguer sD w nuelD eins uryD iliz ethD uigD edro nd othk mmD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 28 publications
(51 reference statements)
0
41
0
Order By: Relevance
“…ARR has been commonly used as a primary efficacy endpoint in phase 3 MS clinical trials . Because of data overdispersion, negative binomial regression is often used to analyze the data . In cases with excessive 0 counts, the ZIP and zero‐inflated negative binomial models are gaining popularity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARR has been commonly used as a primary efficacy endpoint in phase 3 MS clinical trials . Because of data overdispersion, negative binomial regression is often used to analyze the data . In cases with excessive 0 counts, the ZIP and zero‐inflated negative binomial models are gaining popularity .…”
Section: Discussionmentioning
confidence: 99%
“…30 Because of data overdispersion, negative binomial regression is often used to analyze the data. 5,[31][32][33] In cases with excessive 0 counts, the ZIP and zero-inflated negative binomial models are gaining popularity. [31][32][33][34] However, there are some limitations of zero-inflated models.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have demonstrated that distributions other than the Poisson may be more applicable to yields of chromosome aberrations (e.g. Ainsbury et al 2013;Higueras et al 2015, Oliveira et al 2016, for example, and thus it is possible that radiation dose estimates may be more accurately described by alternative distributions to the Poisson. The Bayesian approach allows much more accurate characterization of the dose distribution as it is based on the combined information regarding the potential dose and exposure scenario, the calibration coefficients and the yield of aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al. () investigate data on the number of chromosome aberrations in cytogenetic biodosimetry. Given the discrete nature of the response, this paper offers a bridge between well‐established modeling techniques in the zero‐inflated count data context, and the extension of such methodologies to the wider context of semicontinuous data.…”
mentioning
confidence: 99%
“…These articles cover different areas, all of interest to the biometric community, and give insights and suggestions on how such kind of situations can be efficiently handled. Oliveira et al (2016) investigate data on the number of chromosome aberrations in cytogenetic biodosimetry. Given the discrete nature of the response, this paper offers a bridge between well-established modeling techniques in the zero-inflated count data context, and the extension of such methodologies to the wider context of semicontinuous data.…”
mentioning
confidence: 99%